Particulate suspension: a review of studies characterizing particulates and volatile organic compounds emissions during additive manufacturing processes. (3rd April 2023) - Hossain, Sayed Kaes Maruf; Toledo Vega, Azul; Valles-Rosales, Delia; Park, Young Ho; Kuravi, Sarada; Sohn, Hansuk
Abstract: As additive manufacturing (AM) has become an evolving discipline in many industries, including manufacturing, medical, and aerospace, it becomes important to identify the risk coming from human exposure to particulates and Volatile Organic Compounds (VOCs) in AM which can lead to serious and chronic health issues. To address this issue, this article first provides a summary of previously reported particulate and VOCs characterization studies during AM processes, including equipment, environmental setups, variables studied, and instrumentation reported in the literature. We then reported a synopsis of the nature of the exposure, characteristics of the emitted particulates and VOCs, and associated health risks for different AM settings in a systematic manner. The key factors contributing to the harmful emissions include the use of toxic material compounds, high operating temperature, manual handling of hazardous materials, and limitations of the underlying printing technology among others. For that matter, we have outlined potential pathways to control hazardous exposure. Our recommendations include adopting safer operational practices, developing regulatory frameworks for facilities and equipment manufacturers, and seeking better technologies that minimize harmful emissions. Our aim is to benefit early-stage researchers, regulators, and industry practitioners in understanding and advancing knowledge of health hazards, safer practices, and technologies in AM.